Added Value Analysis and Development Strategy of Tobacco Stem Waste Treatment Into Briquettes (Case Study at Jember Tobacco Research Center) - Wardhana, Danu Indra; Setiawan, Andika Putra; Riskiyono, Syahroni (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2026)
Tobacco is one of the plantation commodities that has a strategic role in the national economy. Currently, tobacco stem waste is largely underutilized and inadequately managed at the farm level. Tobacco waste is processed into briquettes to achieve high economic value. Currently, tobacco briquettes are still rarely produced by the community; they are still produced by the Jember Tobacco Research Center. The objectives of this study are: (1) Analyzing the amount of added value produced in the processing of tobacco stem waste into briquettes at the Jember Tobacco Research Center. (2) Determine alternative strategies in the development of the briquette agro-industry at the Jember Tobacco Research Center. (3) Determine strategic priorities for the development of the briquette agro-industry at the Jember Tobacco Research Center. The data analysis methods used in this study are the Hayami method, SWOT analysis, and the AHP method. In this study, tools include questionnaires, laptops, cameras, and Microsoft Excel. Based on the Hayami value-added analysis, tobacco stem briquette processing yields an added-value ratio of 59%, indicating a high level of value addition. The results of the SWOT analysis indicate quadrant I, which means that the company is in a very favorable position. In addition to the AHP results, four alternative strategies were identified from the SWOT quadrant, each with four criteria equally connected to it. The results of the managerial implications obtained from the AHP method indicate that the priority of the resulting strategy is to collaborate with tobacco-based companies to ensure briquette products are ready for commercialization to the public, so they are widely known from farmers to entrepreneurs.